PERAN LINGKUNGAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA CV.TIRTA SASMITA PAMULANG TANGERANG SELATAN - Agustina Mogi; Ansori Akbar (Al Hasanah Barokah Foundation, 2025)
This study aims to examine the role of the work environment in improving employee performance at CV. Tirta Sasmita Pamulang, a company engaged in the production and distribution of mineral water. The research uses a qualitative descriptive approach, with data collection techniques including observation, interviews with 7 informants who are employees of CV. Tirta Sasmita Pamulang, and documentation. The results of the study show that the work environment, which includes physical aspects (such as workspace layout and supporting facilities) as well as non-physical aspects (such as employee relations and communication with superiors), has a significant influence on employee performance. A conducive work environment has been proven to enhance work spirit, efficiency, and employee productivity. This study recommends that the company pay greater attention to workplace comfort and improve internal communication in order to achieve optimal work outcomes.